2020
DOI: 10.14734/pn.2020.31.3.129
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Interventions and Clinical Outcomes of Patients with Trisomy 18: a Single Center Experience

Abstract: The purpose of this study was to investigate the impact of surgical interventions on the survival rate of the trisomy 18 and to provide the clinical information of the developmental status of the neonatal intensive care unit (NICU) survivors. Methods: We retrospectively reviewed the medical records of the patients who were confirmed genetically as trisomy 18 in a tertiary hospital. Patients were divided into those who were treated with active surgical interventions and those who were not (the control group). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…However, it was observed that procedures in Korea were relatively performed in the early life stages. Two single referral center studies conducted in Korea reported an increasing proportion of children with T18 receiving active treatment after birth [ 17 , 18 ]. In one study, positive pressure ventilation and intubation were performed in 79.2% and 54.2% of children with T18, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it was observed that procedures in Korea were relatively performed in the early life stages. Two single referral center studies conducted in Korea reported an increasing proportion of children with T18 receiving active treatment after birth [ 17 , 18 ]. In one study, positive pressure ventilation and intubation were performed in 79.2% and 54.2% of children with T18, respectively [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two single referral center studies conducted in Korea reported an increasing proportion of children with T18 receiving active treatment after birth [ 17 , 18 ]. In one study, positive pressure ventilation and intubation were performed in 79.2% and 54.2% of children with T18, respectively [ 17 ]. Furthermore, another study reported that 77.2% were intubated, higher than those in previous studies [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation